Evolution of the East Asian monsoon and its response to uplift of the Tibetan Plateau since 1.8 Ma recorded by major elements in sediments of the South China Sea - Meng, XianWei; Xia, Peng; Zheng, Jun; Wang, XiangQin (Chinese science bulletin, 2011)
Evolution of the East Asian monsoon and its response to uplift of the Tibetan Plateau has been investigated in the study of global change. Core sediment samples drilled in the South China Sea during ODP Leg184 are the best materials for studying long-term variability of the East Asian monsoon. R-mode factor analysis of major elements in the fine grain-sized carbonate-free sediments （〈4 I.tm） of the upper 185 mcd splice of ODP Site 1146 drilled during Leg184 in the South China Sea shows that Ti, TFe203, MgO, K20, P, CaO, and A1203 are representative of a terrestrial factor. The variation in the terrestrial factor score is subject to chemical erosion in the source region and thus indicates the evolution of the East Asian summer monsoon. The terrestrial factor score has three stepwise decreases at ~1.3 Ma, ~0.9 Ma, and -0.6 Ma, indicating the phased weakening of the East Asian summer monsoon is related to wholly stepwise, quick uplifts of the Tibetan Plateau since 1.8 Ma. The periodic fluctuation of the terrestrial factor score since ~0.6 Ma indicates that the glacial-interglacial cycles have been the main force driving the evolution of the East Asian monsoon. As in the case of Chinese loess, the long-term evolution of the East Asian monsoon recorded in sediments of the South China Sea reflects a coupled effect of the glacial-interglacial cycle and uplift of the Tibetan Plateau.